ANALISIS RETURN SAHAM BLUE CHIP DAN NON BLUE CHIP TERHADAP SAHAM YANG TERGABUNG DALAM INDEKS LQ45 DI BURSA EFEK INDONESIA TAHUN 2015 - budiarti, endah; ningsih, ratna; penangsang, parikesit (JEM17: Jurnal Ekonomi Manajemen, 2017)
ABSTRAKWhen first investing in stock securities on the Stock Exchange, an investor will experience confusion in choosing what stocks can generate future profits. While in the market there are stock companies that have a long history as a Market Leader. Its products are very popular with consumers. Thus the level of profits of large companies and will continue to increase. Such shares are called Bluechips, while companies whose products are not Market Leaders are categorized as Non Bluechips shares. Based on research conducted on return (profit rate) on stocks that categorized Bluechips and Non Bluechips can be analyzed that during observation of shares of Bluechips included in LQ 45 year 2015 yield negative Average return equal to -0.000550324 but if tested statistically return is not different from zero. While Non Bluechips share return produces a larger return, but if tested statistically also shows results that are not different from zero. It can be concluded that investing in both Bluechips and Non Bluechips shares is the same. However, it is nominally more profitable to invest in Non Bluechips shares.Â Keyword : Return, Bluechips,Â  Non Bluechips